2020
DOI: 10.1002/der2.7
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical facial tightening after a fractional noninsulated microneedling radiofrequency treatment in Asians

Abstract: Background: As our previous three-dimensional (3D) volumetric investigations have shown, noninsulated microneedle radiofrequency (NIMNRF) with 2.5-mm penetration depth needles can induce long-lasting tightening effects. However, further tightening effects for deeper tissues were sometimes required. The objective of this study was to investigate the efficacy of a novel fractional NIMNRF treatment strategy with 5.0-mm penetration depth needles.Materials and Methods: Twenty Asian patients underwent full facial sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…RF devices offer a non‐invasive way to improve wrinkles with little side effects and no downtime. Previous studies about periorbital rhytids, that have been treated by different types of RF devices, have been published . In this study, the VISIA device allowed us to document the minimal changes in periorbital wrinkles, and wrinkle score was calculated with the aid of a computer software that provided us with a 3D photo for close wrinkles observations.…”
Section: Discussionmentioning
confidence: 99%
“…RF devices offer a non‐invasive way to improve wrinkles with little side effects and no downtime. Previous studies about periorbital rhytids, that have been treated by different types of RF devices, have been published . In this study, the VISIA device allowed us to document the minimal changes in periorbital wrinkles, and wrinkle score was calculated with the aid of a computer software that provided us with a 3D photo for close wrinkles observations.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve months after treatment, using the same three-dimensional volumetric assessment method, 15 of the study subjects showed significant volume reduction in the nasal and perioral region, demonstrating longlasting effect. 33 A multicenter trial for midface and lower face skin rejuvenation in which 49 patients received 3 monthly treatments demonstrated that 100% had improvement and 65% had significant improvement on the Global Aesthetic Improvement Scale, and there was a significant reduction in wrinkles and improvement in skin texture at 3 months on the Fitzpatrick Wrinkle and Elastosis Scale. 34…”
Section: Intensif (Endymed Caesarea Israel)mentioning
confidence: 99%
“…However, a larger heated area may cause epidermal damage, leading to a higher risk of pigmentation, and prolonged downtime. 9,10 FMR is categorized into negative and nonnegative pressure based on the presence or absence of a negative pressure device in the therapeutic hand. It has been well documented that the nonnegative pressure FMR can be used to improve facial skin aging, acne and acne scars, primary axillary hyperhidrosis, and androgenetic alopecia.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐insulated microneedles transfer energy along the entire needle body, and the radiofrequency heating area is significantly larger than that of insulated microneedles, resulting in better clinical efficacy. However, a larger heated area may cause epidermal damage, leading to a higher risk of pigmentation, and prolonged downtime 9,10 …”
Section: Introductionmentioning
confidence: 99%